Combined effects of low-intensity blood flow restriction training and high-intensity resistance training on muscle strength and size - Yasuda, T.; Ogasawara, R.; Sakamaki, M.; Ozaki, H.; Sato, Y.; Abe, T. (European Journal of Applied Physiology, 2011)
We investigated the combined effect of low-intensity blood flow restriction and high-intensity resistance training on muscle adaptation. Forty young men (aged 22-32 years) were randomly divided into four groups of ten subjects each: high-intensity resistance training (HI-RT, 75% of one repetition maximum [1-RM]), low-intensity resistance training with blood flow restriction (LI-BFR, 30% 1-RM), combined HI-RT and LI-BFR (CB-RT, twice-weekly LI-BFR and once-weekly HI-RT), and nontraining control (CON). Three training groups performed bench press exercises 3 days/week for 6 weeks. During LI-BFR training sessions, subjects wore pressure cuffs on both arms that were inflated to 100-160 mmHg. Increases in 1-RM were similar in the HI-RT (19.9%) and CB-RT (15.3%) groups and lower in the LI-BFR group (8.7%, p < 0.05). Maximal isometric elbow extension (MVC) increased in the HI-RT (11.3%) and CB-RT (6.6%) groups; there was no change in the LI-BFR group (-0.2%). The cross-sectional area (CSA) of the triceps brachii (TB) increased (p < 0.05) in the HI-RT (8.6%), CB-RT (7.2%), and LI-BFR (4.4%) groups. The change in relative isometric strength (MVC divided by TB CSA) was greater (p < 0.05) in the HI-RT group (3.3%) than in the LI-BFR (-3.5%) and CON (-0.1%) groups. Following training, relative dynamic strength (1-RM divided by TB CSA) was increased (p < 0.05) by 10.5% in the HI-RT group and 6.7% in the CB-RT group. None of the variables in the CON group changed. Our results show that low-intensity resistance training with BFR-induced functional muscle adaptations is improved by combining it with HI-RT.